Los recursos didácticos para desarrollar la animación a la pre lectura dirigido a niños y niñas de 5 a 6 años de edad en la Unidad Educativa “Juan Abel Echeverría” de la parroquia San Felipe, cantón Latacunga, provincia Cotopaxi en el periodo 2014- 2015 - Quishpe Quishpe, Angélica Piedad (2016)
This experience is born by the desire to lead a leisurely approach to children's books, as a response to the problem of lack of reading habits in children beyond school requirements. From this point we worked with multivariate methodologies through, the game. By implementing these activities the result was the encounter and discovery of a range of endless possibilities of work in addition to the reading motivation, among which he found that children are more sympathetic to concepts of equal opportunities, respect for the natural environment, health and human rights. Likewise, it encourages children issuing its word and creating stories written by them is possible. The objectives are described in a feasible and optimized way, justify the validity of this thesis with sufficient arguments. The theoretical and practical foundation in cooperation with the research development has helped formulate conclusions and recommendations that define the solution of the problem and the respective thesis.